Long term survival effect of metoprolol in dilated cardiomyopathy. Issue 4 (1st April 1998) - Di Lenarda, A; De Maria, R; Gavazzi, A; Gregori, D; Parolini, M; Sinagra, G; Salvatore, L; Longaro, F; Bernobich, E; Camerini, F
Abstract : Objective: To evaluate the additive effect of metoprolol treatment on long term incidence of fatal and non-fatal cardiac events in idiopathic dilated cardiomyopathy. Design: 586 patients with idiopathic dilated cardiomyopathy were prospectively enrolled in a multicentre registry and followed up for a mean (SD) of 52 (32) months. Metoprolol, carefully titrated to the maximum tolerated dose, was added to conventional heart failure treatment in 175 patients. Results: Survival and transplant-free survival at seven years were significantly higher in the 175 metoprolol treated patients than in the remaining 411 on standard treatment (81% v 60%, p < 0.001, and 69% v 49%, p < 0.001, respectively). By multivariate analysis, metoprolol independently predicted survival and transplant-free survival (relative risk reduction values for all cause mortality and combined mortality or transplantation 51% (95% confidence interval 21% to 69%), p = 0.002, and 34% (5% to 53%), p = 0.01, respectively). New York Heart Association class, left ventricular end diastolic diameter, and pulmonary wedge pressure were also predictive. Seven year survival (80% v 62%, p = 0.004) and transplant-free survival (68% v 51%, p = 0.005) were significantly higher in 127 metoprolol treated cases than in 127 controls selected from the entire control cohort and appropriately matched. Metoprolol was associated with a 30% reduction in all cause mortality (7% to 48%, p = 0.015) and a 26% reduction in mortality or transplantation (7% to 41%, p = 0.009). Conclusions —The addition of metoprolol to standard heart failure treatment, including angiotensin converting enzyme inhibitors, was effective in the long term, reducing both all cause mortality and transplantation in patients with idiopathic dilated cardiomyopathy.